THE URGENCY FOR REGIONAL INTEGRATION IN ACCORDANCE TO INVESTMENT RISK MANAGEMENT - Yuniarti, Yuniarti (UI Scholars Hub, 2016)
Investment is an activity which is needed by every country, especially in development country. However, the investment activity itself also brings in some risk which is called as investment risk. These investment risks usually recognized to be covered by an investment agency to protect the investor. Multilateral investment guarantee agency (MIGA) is usually used to maintained and cover the loose of investor. But, actually among the investment risks which are identified by MIGA will only responsible for the market risk, meanwhile the biggest lost for investor also came from political and financial risks which have to be recognized in advanced. This is where the export credit agency will take place. Nevertheless, there are still many loops to be identified to determine the characteristic of export credit agency itself. To deal with those kinds of risks, a regional integration is needed to avoid an overlapping regulation among ASEAN Economic Communiy. Thus, will lead to a common perception on how to treat those risks and who will be responsible to cover it.